Land uprising : Native story power and the insurgent horizons of Latinx indigeneity - Trujillo, Simón Ventura (The University of Arizona Press, 2020)
"As a work of ethnic cultural studies of the Americas, Land Uprising examines the cultural production of social activism arising from struggles to reclaim land in contested colonial contexts. The author, Simón Trujillo, who is from New Mexico, focuses on the cultural politics and production of La Alianza Federal de Mercedes, a 1960s activist group in New Mexico that sought to reclaim Spanish lands transferred to the United States via the Treaty of Guadalupe Hidalgo. By examining the cultural production of La Alianza alongside Pueblo writing, Chicana feminist thought, and Indigenous activism in Mexico, Trujillo argues for the power of land reclamation as a way of re-evaluating the relationship between modernity, sovereignty, and indigeneity that is irreducible to the more familiar racial politics of Chicana/o, Mexican, and US nationalism"--